Business Analysis with Microsoft® Excel, Second Edition - Carlberg, Conrad (Que, 2001)
Take control of the bottom line using expert techniques and Excel's powerful financial capabilities! Whether you own a small business or work for a large corporation; whether you are looking for help making financial and business decisions -- this book is for you. Business Analysis with Microsoft Excel, Second Edition provides in-depth information that will maximize your use of the tools within Excel. Professional advice and guidance from an experienced author provide the answers to your most pressing questions.